Pengaruh Stigmatisasi Sosial Terhadap Koping Stress Perawat dalam Penanganan Covid-19 di Rumah Sakit dr. Soedjono Magelang - Tri Winugroho; Arief Budiarto; Arip Hidayat (NERS Jurnal Keperawatan)
During the Covid-19 pandemic, Indonesia also faced a tendency to increase the number of cases. Stigma that arises from the community both to patients and health workers will actually have an impact on nurses' psychology such as feelings of guilt, anxiety, fear, feeling as a source of disease transmission. The purpose of this study was to analyze the effect of social stigma on nurses' coping with stress in handling Covid-19.